Introducing Climate and Agriculture Network for Africa (CANA) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The Climate and Agriculture Network for Africa (CANA) is a knowledge sharing web-based platform by a network of partners drawn from the region. It brings together researchers, policy makers and practitioners within climate science and agriculture who are seeking to build resilience within Africa. Join our network today: http://canafrica.com/ Read more: https://ccafs.cgiar.org/blog/introducing-africa%E2%80%99s-bridge-between-science-and-policy